2007
DOI: 10.1109/iembs.2007.4353446
|View full text |Cite
|
Sign up to set email alerts
|

Classification of Motor Activities through Derivative Dynamic Time Warping applied on Accelerometer Data

Abstract: In the context of tele-monitoring, great interest is presently devoted to physical activity, mainly of elderly or people with disabilities. In this context, many researchers studied the recognition of activities of daily living by using accelerometers. The present work proposes a novel algorithm for activity recognition that considers the variability in movement speed, by using dynamic programming. This objective is realized by means of a matching and recognition technique that determines the distance between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(45 citation statements)
references
References 19 publications
0
45
0
Order By: Relevance
“…In recent years, many papers have surfaced involving gesture recognition using accelerometers [20], [21]. Devices such as the WiiMote are able to provide raw sensor data to PCs wirelessly, making them advantageous to research.…”
Section: B Gesture Recognitionmentioning
confidence: 99%
“…In recent years, many papers have surfaced involving gesture recognition using accelerometers [20], [21]. Devices such as the WiiMote are able to provide raw sensor data to PCs wirelessly, making them advantageous to research.…”
Section: B Gesture Recognitionmentioning
confidence: 99%
“…Most of previous researches [6] [7] [11] used decision tree algorithm (C4.5) for recognizing stereotypical motor movements to identify the autistic child but Muscillo et al [19] displayed that DTW is better than C4.5 when they compared between them. As mentioned before, stereotypical motor movements are not enough to identify the autistic child therefore they were not in consideration, however we compared hand flapping detection accuracy in both cases when DTWDir achieved highest, and lowest accuracy using three axes together, and Z-Axis respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The data are collected from two subjects -female, male-and they found that the mean accuracy of DTW is 91% even though the dataset training size is small. Muscillo et al [19] compared between decision tree C4.5 and DTW classifiers for recognizing low-level food preparation activities. The data are collected from four sensors equipped kitchen utensils (knifes and spoon) about 6 hours.…”
Section: Living Activitiesmentioning
confidence: 99%
“…Dynamic time warping (DTW) is an algorithm for measuring similarity between two signals which may vary in time or speed [12]. It has been used successfully to classify activities that have a cyclic pattern.…”
Section: Dynamic Time Warpingmentioning
confidence: 99%